Students' opinion on the transition from EFL to ELF: Revisiting English pedagogy in vocational higher education - Sariani, Sariani; El Khairat, Mutia; Marzuki, Dony; Fitria, Novi; Damaiyanti, Muthia; Astuti, Indri; Binti Yusof , Ts Ummu Hani (JEES (Journal of English Educators Society), 2026)
As workforce diversity increases in the globalization era, vocational education plays a crucial role in preparing students to be competent and industry-ready, with English serving as a key medium for professional integration. English as a Lingua Franca (ELF) has emerged as a flexible mode of communication, facilitating interaction not only between native and non-native speakers but also among non-native speakers from varied linguistic backgrounds. This study examines the perceptions of Indonesian Vocational Higher Education (VHE) students regarding the role and relevance of ELF in meeting global workplace communication demands. Participants consisted of sixty-nine sixth-semester English majors who had completed two- to three-month internships in various industries. Data were collected through a five-point Likert-scale questionnaire and semi-structured interviews, enabling both quantitative and qualitative insights. Statistical analysis using a t-test, following the Shapiro-Wilk normality test, revealed mean differences ranging from M = 2.95 (Q10) to M = 4.28 (Q14). These findings were supported by interview data, indicating that most participants viewed ELF as more suitable for workplace communication than traditional English as a Foreign Language (EFL) norm. The study highlights the need to align English Language Teaching (ELT) in vocational education with ELF-oriented principles to enhance communicative effectiveness in global professional settings.